Participatory processes and the evolution of environmental agendas in estuary restoration: the Maketū case. Issue 3 (3rd July 2022) - Barrett, Patrick; Kurian, Priya; Cretney, Raven; Blackett, Paula; Le Heron, Erena; Le Heron, Richard
ABSTRACT: The article analyses participatory processes in estuary restoration in Maketū on the East Coast of the North Island to examine how evolving relational dynamics amongst key stakeholders and Māori led to the achievement of a collective environmental imaginary. The case, marked by a history of conflict over the diversion of the Kaituna River and resulting estuary degradation, led to a focussed period of community engagement between 2006 and 2009 which established a collective intention to restore the ecological health of the estuary. Ongoing community engagement has been a feature of restoration project design and implementation. In examining this case, we draw on the concept of imaginaries, referring to shared visions of desirable futures, to explore how 'imaginaries of process' and 'imaginaries of outcome' played out among a heterogeneous set of stakeholders and Indigenous actors. We undertake a discourse analysis of relevant documents and of interviews and focus groups with 25 participants to demonstrate how inclusive participatory processes were used as a technique to resolve estuary degradation, address historical grievance between Māori, the community and local authorities, and reset the governance and management relationships between these actors.